The University Administrative Staff Perception of Inclusion in Higher Education - Nīmante, Dita; Baranova, Sanita; Stramkale, Ligita (Acta Paedagogica Vilnensia, 2021)
This study investigates university administrative staff perception of inclusion in higher education at the university level. The study uses the University of Latvia as a case to answer the following research questions: What constitutes inclusion in university education, how accessibility is provided? What are the support systems provided for diverse students? What support and training are provided to administrative and academic staff to ensure that the educational needs of diverse student bodies are met? The methodology employed is exploratory and descriptive, and uses the interview method and semi-structured questionnaire. The sample is made of seven administrative staff members representing all levels of administration in the University. Findings suggest that administrative staff members perceive inclusion as a new principle for HE, where diversity is perceived in its broader sense. Findings indicate that support is provided to all students, but that the support is not designed specifically for students with diverse needs. Findings suggested that none of the administrative staff or academics had received training on how to address student diversity.
Keywords: inclusion; perception; higher education; University of Latvia